호텔구성원의 팔로워십이 서비스지향성에 미치는 영향 - 이상우(Sang-Woo Lee) (한국콘텐츠학회 논문지, 13(6), 2013)
This study aims to suggest implications on hotel HR management through the research on the influence relation with voluntary behaviors that increase the effectiveness of work functions and also hotel employee' perceived followership contributing to achievement of hotel's goals. As study methods to achieve the study objective suggested above, we aim to conduct literature research and empirical study. The data are analyzed by such frequency analysis, validity analysis, reliability analysis, correlation analysis, confirmatory factor analysis, covariance structure analysis. The SPSS 10.1 and AMOS 4.0 for Windows program was used to investigate material. The major finding can be summarized as follow: The analysis on relationship between followership and revealed that 'critical thinking' and 'enthusiasm' dimensions of but 'active participation' dimension of followership has not affected service orientation. The expected effects through this study are like below. First, it is expected that the theory about followership will be extended by verifying the causal relation between followership and internal mental state. Second, it is also expected to be able to suggest alternatives for qualitative improvement of service and emphasis of the importance of hotel employee'. 본 연구의 목적은 업무의 효과적 기능을 높일 수 있는 호텔구성원의 자발적 행동 연구를 통하여 호텔의 목표달성에 기여할 수 있는 호텔 인적자원관리의 시사점을 제시하는 것이다. 연구목적을 달성하기 위한 연구방법으로 문헌연구와 실증연구 두 가지 방법을 차례로 진행하고자 한다. 수집된 자료는 빈도분석, 타당성분석, 신뢰성분석, 상관관계 분석, 확인적 요인분석, 공분산 구조분석을 실시하였다. 분석은 SPSS 10.1과 AMOS 4.0 통계패키지를 활용하였으며, 중요한 결과를 제시하면 다음과 같다. 팔로워십의 구성요인 중 비판적 사고와 열정 요인은 서비스지향성에 유의적인 영향관계를 나타냈다. 반면 능동적 참여 요인은 서비스 지향성에 유의적인 영향관계를 나타내지 않았다. 이 연구를 통한 기대효과는 다음과 같다. 첫째, 팔로워십과 관련된 심리적 요인의 검증을 통하여 팔로워십에 대한 이론을 다양화 할 수 있다. 둘째, 호텔구성원의 중요성을 강조하여 서비스의 질을 향상 시킬 수 있는 대안을 제시하였다.